Implementasi Penyetaraan Jabatan Administrasi Tenaga Kependidikan ke Jabatan Fungsional - timur, Widya; Fauzi, Amin; Yakup, Yakup; Satyawati, Tara (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
Since the government launched a policy on simplifying the level of bureaucracy and government administration in the next five years that focuses on human resource development, the Ministry of PAN RB has developed an achievement strategy, namely, transfering administrative/structural positions of echelon III and echelon IV into functional positions. This transfer of positions has caused anxiety and feeling of uncertainy among officials whose current positions will be transferred. In its implementation, problems arise such as the readiness of administrative employees who are transferred into functional positions, their division of work, and their performance appraisal. This study aims to assess the implementation of the policy of transfering administrative positions to functional positions at the State University of Surabaya. This research is a qualitative research, using data collection methods with interviews, observations, and documentation. The results of this study indicate that the implementation of transfer at the State University of Surabaya has been carried out properly according to the regulation, but there are still cases of mismatch between educational background and the functional positions and cases of mismatch between functional positions with the placement within the working units which cause a lack of positive impact on their work records and a decrease in financial support.